Video data from video CTD deployments during POSEIDON cruise POS534, with links to files - Linke, Peter (GEOMAR - Helmholtz Centre for Ocean Research Kiel, 2019)
The environmental background hydrography of the Goldeneye area North Sea was determined by a video guided water sampler rosette/CTD system. The system was used to perform vertical profiles along the water column and near seafloor observations via towing. The CTD system (SBE 9) unit included additional pH (SBE27), O2 (SBE43) and altimeter (PSA-916, Teledyne Benthos) sensors. On POS534 cruise, an HD-Video camera and light sources were attached to the lower part of the frame providing video footage of the near seafloor (Linke et al., 2015) during a gas release experiment at different CO2-release rates. Far field (background) data was recorded during VCTD stations 3-6 and 9-11. Near field measurements and video-observations were performed during VCTD 7, 8, and 12.